An investigation into Universiti Teknologi MARA pre-commerce students’ perspectives on second language learning / Caesar Dealwis, Baljinder Singh Maghar Singh and Sueb Ibrahim - Dealwis, Caesar; Maghar Singh, Baljinder Singh; Ibrahim, Sueb (ACRULeT, Faculty of Education & UiTM Press, 2007)
This paper reports on an exploratory study which aims to investigate learners’ perceptions on language learning in two UiTM campuses in the state of Sarawak. The researchers were guided by the research question – What are the ideas of UiTM students on language learning in terms of the following aspects: the usefulness of the various language learning activities; the nature of language learning; the ideal language learning situation; and how they learn English. The study also aimed to find out if there are differences in students’ perceptions, in particular between male and female, and between students in Mukah and Samarahan campuses respectively. The findings indicate that the respondents from both campuses do possess diverse perspectives on language learning, thus reflecting their different learning styles and orientations